2016
DOI: 10.1111/are.13156
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on immunomodulatory and growth enhancing effects of three prebiotics (galactooligosaccharide, fructooligosaccharide and inulin) in common carp (Cyprinus carpio)

Abstract: This study investigated the effects of different prebiotics, including galactooligosaccharide (GOS), fructooligosaccharide (FOS) and inulin (INL), on skin mucosal immune parameters, humoral immune responses as well as performance of common carp (Cyprinus carpio). Two hundred and forty specimens (13.85 ± 0.85 g) were stocked in 12 fibreglass tanks assigned into three treatments and a control group. The experimental diets were formulated to have equal level (2%) of the prebiotics. At the end of the feeding trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 67 publications
2
37
0
Order By: Relevance
“…plantarum 7–40 in the diet did not promote L. vannamei growth (Chiu et al., ). It may be suggested that GOS was used as substrate and then modulated the intestinal microbiota towards beneficial bacteria and subsequently increased production of short chain fatty acids (SCFAs), digestive enzyme activity and improved gut health and nutrient absorptive ability in shrimp (Hoseinifar, Zoheiri, Dadar, Rufchaei, & Ringø, ; Hoseinifar, Ahmadi, Raeisi et al., ; Huynh et al., ). In addition, the increased growth performance of shrimp fed SYN diet was involved with increased feed intake, which was in agreement with the observations of tilapia (Hassaan, Soltan, & Ghonemy, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…plantarum 7–40 in the diet did not promote L. vannamei growth (Chiu et al., ). It may be suggested that GOS was used as substrate and then modulated the intestinal microbiota towards beneficial bacteria and subsequently increased production of short chain fatty acids (SCFAs), digestive enzyme activity and improved gut health and nutrient absorptive ability in shrimp (Hoseinifar, Zoheiri, Dadar, Rufchaei, & Ringø, ; Hoseinifar, Ahmadi, Raeisi et al., ; Huynh et al., ). In addition, the increased growth performance of shrimp fed SYN diet was involved with increased feed intake, which was in agreement with the observations of tilapia (Hassaan, Soltan, & Ghonemy, ).…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we hypothesized that screening of prebiotics should be considered before developing a synbiotic to induce higher effects on the growth of L. vannamei . Hence, three prebiotics, which are commonly used in aquaculture, including MOS (Zhang et al., ), FOS (Hoseinifar, Eshaghzadeh, Vahabzadeh, & Mana, ; Hoseinifar, Ahmadi, Khalili et al., ; Hoseinifar, Ahmadi, Raeisi et al., ; Li et al., ; Soleimani, Hoseinifar, Merrifield, Barati, & Abadi, ; Wu et al., ) and GOS (Hoseinifar, Khalili, Rostami, & Esteban, ; Hoseinifar, Mirvaghefi, Amoozegar, Sharifian, & Esteban, ; Hoseinifar, Zoheiri et al., ; Miandare, Farvardin, Shabani, Hoseinifar, & Ramezanpour, ; Yousefi, Hoseinifar, Paknejad, & Hajimoradloo, ), were screened for utilization by the probiotic Lac. plantarum 7–40 in vitro in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there were no significant increases in survival rate of turbot, beluga, rainbow trout or juvenile Nile tilapia following dietary supplementation with either inulin or FOS (Mahious et al., ; Ortiz et al., ; Reza et al., ; Tiengtam et al., ). Dietary supplementation of inulin or FOS led to increase survival rate of common carp fry (0.55 g body weight), whereas the significant improvement of survival rates was not observed in common carp during later growth phase (13.85 g body weight) (Eshaghzadeh et al., ; Hoseinifar et al., , ). Although supplementation with dietary FOS did not significantly increase the survival rate of Caspian roach, it did significantly enhance their survival rate when the fish were exposed to salinity stress (Soleimani et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In beluga, dietary inulin had negative effects on growth response and resulted in a decrease in total protein in blood (Reza et al., ). In common carp, while dietary GOS and inulin led to increase plasma protein, dietary FOS did not significantly alter plasma protein (Hoseinifar et al., ), demonstration that different prebiotic type would affect different prebiotic metabolism. In rat, while dietary JA led to decrease blood glucose, it did not alter blood cholesterol, triglycerides, total protein and albumin (Samal et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation